2014
DOI: 10.1039/c4ob00662c
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flow chemistry: a discovery tool for new chemical reactivity patterns

Abstract: A new reactivity pattern and extended reaction scope has been obtained by transferring a reaction from batch mode to flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 42 publications
(13 reference statements)
0
43
0
1
Order By: Relevance
“…Interesting examples relative to drug development are proposed by Roberge et al [16]. Results relative to reaction paths unrealizable in batch mode are also presented [17]. Finally, flow chemistry has been very effectively described as a way to expand the process window [11,12].…”
mentioning
confidence: 99%
“…Interesting examples relative to drug development are proposed by Roberge et al [16]. Results relative to reaction paths unrealizable in batch mode are also presented [17]. Finally, flow chemistry has been very effectively described as a way to expand the process window [11,12].…”
mentioning
confidence: 99%
“…The aim of this Communication is to demonstrate that recent advances in flow chemistry, particularly the development of self-optimizing reactors, not only can accelerate the identification of byproducts but also can lead to the discovery of unexpected reactions. [3] Self-optimizing reactors combine a computer-controlled continuous reactor with in-line analysis to adjust reaction conditions automatically to control the outcome of the reaction, [4] see Figure 1. We have previously demonstrated that, for a reaction that can give rise to two different products, such a reactor can be optimized to maximize the yield of either product.…”
Section: Introductionmentioning
confidence: 99%
“…6 In recent times, transition metal chemistry has dominated C-C bond cross-coupling strategies. [7][8][9][10][11][12][13] This powerful approach has been central to the planning and execution of modern synthesis programs both in academia and industry.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] While many such sequences are known, there is still room to exploit new reactivity patterns and different chemical combinations derived from reactive intermediates. 6 In recent times, transition metal chemistry has dominated C-C bond cross-coupling strategies. [7][8][9][10][11][12][13] This powerful approach has been central to the planning and execution of modern synthesis programs both in academia and industry.…”
Section: Introductionmentioning
confidence: 99%